2017
DOI: 10.3847/1538-4357/aa9277
|View full text |Cite
|
Sign up to set email alerts
|

MAXI J1957+032: An Accreting Neutron Star Possibly in a Triple System

Abstract: I present an optical characterization of the Galactic X-ray transient source MAXI J1957+032. This system flares by a factor of 10 4 every few hundred days, with each flare lasting ∼5days. I identify its quiescent counterpart to be a late-K/early-M dwarf star at a distance of 5±2 kpc. This implies that the peak 0.5 10 keV -luminosity of the system is 10 36.4 0.4  erg s −1 . As found by Mata Sanchez et al. the outburst properties of MAXI J1957+032 are most consistent with the sample of accreting millisecond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…During the brightest outburst of MAXI J1957+032 in 2016, the values of power-law index (Γ) increased from ∼ 1.8 to ∼ 2.5 when the fluxes decreased (outburst 4, Figure 1). From the spectral analysis of MAXI J1957+032, we found that Γ reaches the value close to 2.5 during its three outbursts observed with Swift-XRT (see also Mata Sánchez et al 2017;Ravi 2017;Kennea et al 2017).…”
Section: Spectral Evolution During Outbursts Of Maxi J1957+032mentioning
confidence: 78%
See 3 more Smart Citations
“…During the brightest outburst of MAXI J1957+032 in 2016, the values of power-law index (Γ) increased from ∼ 1.8 to ∼ 2.5 when the fluxes decreased (outburst 4, Figure 1). From the spectral analysis of MAXI J1957+032, we found that Γ reaches the value close to 2.5 during its three outbursts observed with Swift-XRT (see also Mata Sánchez et al 2017;Ravi 2017;Kennea et al 2017).…”
Section: Spectral Evolution During Outbursts Of Maxi J1957+032mentioning
confidence: 78%
“…Another possible cause of these outbursts is mass-transfer variations from the donor similar to that suggested for NGC 6440 X-2 (Heinke et al 2010). If MAXI J1957+032 is a triple star system as proposed by Ravi (2017) one might expect to observe change in the orbital parameters, induced by the distant companion. However, this would need monitoring of future outbursts with more sensitive instruments like XMM-Newton, Chandra.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The available spectroscopic and photometric data do not allow us to determine whether the accretor is a white dwarf, neutron star, or a BH or to discriminate between the two possible interpretations for the M2/3 dwarf: an interloper along the line of sight to the accreting binary or the outer companion in a triple system. We note that two candidate hierarchical triple systems with red dwarf outer companions have been reported in the literature: the 3.5 h orbital period CV RR Pic (Vogt et al 2017) and the LMXB MAXI J1957+032 (Ravi 2017). The best strategy to constrain the compact object nature in CX1004 is to obtain the orbital period through an RV study of the H α emission line.…”
Section: O N C L U S I O N Smentioning
confidence: 99%